Вплив поруватості на трибологічні характеристики електродугових покриттів з порошкових дротів - Студент, М. М.; Ступницький, Т. Р.; Гвоздецький, В. М.; Маркович, С. І.; Мажейка, О. Й.; Student, М.; Stupnickiy, Т.; Gvozdeckiy, V.; Markovich, S.; Mazheyka, А. (КНТУ, 2014)
В статті досліджено вплив поруватості на трибологічні та механічні характеристики еллектродугових покриттів. Визначено, що структурою покриття з порошкових дротів є композит, де чергуються металеві ламелі та ламелі із оксидів, а також пори. Із ростом тиску повітряного струменю розмір структурних складових поверхні покриття та розмір пор зменшується. Встановлено позитивний вплив поруватості на трибологічні характеристики покриттів при терті за граничного мащення. Influence of porosity is investigational the article on mechanical properties of arc coatings. Exposed to research of coatings from different types powder-like. A structure, phase composition, porosity, resistance to the friction, cohesion of coatings depending on pressure of transporting gas, was studied. Determination of coefficient friction of coatings is exposed to research in the conditions of dry friction and border greasing It is set, that from powder-like wires the structure of coatings there is a compo, where metallic lamels and lamels alternate from oxides and also pore. With growth of pressure of air-blast the size of structural constituents of surface of coatings and size of pores diminishes. Positive influence of porosity is set on mechanical properties of coatings in the conditions of border friction. Аrc coatings of gradient type provide high mechanical properties of coatings at to the low level of remaining tensions of in them.
Influence of porosity on mechanical properties of arc coverages from powder-like wires
Keywords: електродугові покриття; порошкові дроти; трибологічні характеристики; зносостійкість; поруватість; elektrometal сoatings; powder-like wires; mechanical properties; firmness to the wear; porosity